Labour Supply and Regional Labour Market Situation - Blien, Uwe; Hirschenauer, Franziska (Raumforschung und Raumordnung | Spatial Research and Planning, 2020)
Germany is particularly affected by demographic change. Therefore, increasing labour market participation is considered an important labour market policy objective because it can counteract shortages of labour supply due to the aging population. The scope for increasing labour force participation is not limited to certain groups of people. It also has a spatial dimension. This paper therefore analyses the regional differences in the labour market participation of men and women of different age groups at the level of German district regions. In particular, we examine regional imbalances in the regional variation of labour force participation. Further relations to regional variables are examined using multiple regressions. The results of the analysis could be interpreted according to the so-called discouragement hypothesis which suggests that unfavourable regional labour market conditions have a negative impact on regional labour force participation. For the regional wage level, only a minimal, mostly positive correlation with the labour force participation can be established, which can be interpreted by the mutually compensating effects of wages. The regional qualification level shows a positive correlation with the participation of middle-aged and older people in the labour market. Finally, further evidence highlights the importance of full-time childcare facilities for the labour force participation of women and, increasingly, men.
Keywords: Labour supply; Labour force participation; Labour force participation rate; Census 2011; German district regions